Pengaruh Self Assessment Terhadap Hasil Belajar Penelitian Tindakan Kelas dan Penulisan Artikel pada Bidang Pendidikan Agama Islam - Lisnawati, Santi; Siregar, Halimah (Universitas Islam Negeri Raden Intan Lampung, 2018)
Assessment of self-ability in learning has benefits to know the advantages and disadvantages of learning. This study aims to determine self-analysis of learning outcomes in CAR courses (classroom action research) on Islamic education subject. The objective this subject is ability to plan, implement and report the result of classroom action research. The method used in this study is the experimental method, namely two classes, each of which is a control and an experimental class. The results showed that there were differences in learning outcomes in class research subjects, the results of data analysis obtained t count value (t hit) that is 3.163 while t table for db 81 and apha 0.05 is t table 1.671, because t count is greater than t table (3.887> 1.671) then Ho is rejected, with Significance (Sig. 2 tailed) of 0.002 that number is less than 0.005 (0.002 <0.005). Thus there is an independent analysis of learning outcomes in CAR courses. CAR learning outcomes will be better if you use self-numbers. Students can easily find out their weaknesses and strengths, make feedback on existing results, and produce something better.